Neointima development in externally stented saphenous vein grafts - Węglarz, Przemysław; Krejca, Michał; Trusz-Gluza, Maria; Bochenek, Krystyna; Konarska-Kuszewska, Ewa; Szydło, Krzysztof; Kuszewski, Piotr; Jackson, Christopher L.; D. Angelini, Gianni; Bajor, Grzegorz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : The main limitation of coronary artery bypass grafting (CABG) is rapid neointimal hyperplasia leading to graft failure. Aim : To assess plaque formation in saphenous vein grafts (SVG) covered by an external Dacron stent in comparison with the classical technique. Material and methods : In the study group vein grafts covered by external stent mesh made of Dacron were implanted. An intravascular ultrasonography (IVUS) study was performed in 35 aorto-coronary SVG covered by an external Dacron stent and in 64 normal SVG during the first year after CABG. In each SVG 25 mm of good quality IVUS image, volumes of lumen, plaque (neointima), outer border of the vein graft (external SVG) and adventitia were calculated in three time periods: 0–130 days, 130–260 days and 260–390 days. Results : Between the first and second time period, lumen volume (mm3) was reduced from 10.33 ±4.4, to 6.80 ±2.23 in the second period and 5.69 ±1.26 in the third one. This effect was much less marked in normal grafts. The corresponding lumen volume (mm3) was: 10.90 ±3.9, 9.15 ±2.94 and 8.92 ±2.93 in consecutive time periods. Plaque volume (mm3) did not change in control grafts during the course of the study, but it increased very significantly in stented grafts from 0.86 ±1.24 in the first period to 2.70 ±1.58 in the second and 3.29 ±2.66 in the third one. Conclusions : The experimental technique of implanting SVG covered with an external elastic Dacron stent seems to be inferior to traditional ones. This is probably due to the more complicated process of vein implantation and higher micro-injury occurrence during the surgery.